2018
DOI: 10.1101/443374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metastatic tumor cells exploit their adhesion repertoire to counteract shear forces during intravascular arrest

Abstract: Cancer metastasis is a process whereby a primary tumor spreads to distant organs.We have previously demonstrated that blood flow controls the intravascular arrest of circulating tumor cells (CTCs), through stable adhesion to endothelial cells. We now aim at defining the contribution of cell adhesive potential and at identifying adhesion receptors at play. Early arrest is mediated by the formation of weak adhesion depending on CD44 and integrin αvβ3. Stabilization of this arrest uses integrin α5β1dependent adhe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…In addition, platelet/fibrin-dependent mechanisms also facilitate tumor cell arrest on the vascular wall and their niching at secondary sites [ 221 , 222 ]. If tumor cells possess receptors (CD44, P-selectin, integrins,...) enabling their adherence to the endothelium [ 223 ], fibrin or platelets may indeed also mediate and strengthen such interactions [ 224 , 225 ].…”
Section: Epithelial–mesenchymal Transitions: Impact On Metastatic mentioning
confidence: 99%
“…In addition, platelet/fibrin-dependent mechanisms also facilitate tumor cell arrest on the vascular wall and their niching at secondary sites [ 221 , 222 ]. If tumor cells possess receptors (CD44, P-selectin, integrins,...) enabling their adherence to the endothelium [ 223 ], fibrin or platelets may indeed also mediate and strengthen such interactions [ 224 , 225 ].…”
Section: Epithelial–mesenchymal Transitions: Impact On Metastatic mentioning
confidence: 99%
“…1b), consistent with the idea 50 that the EC GCX can sterically hinder passage of macromolecules 32 . Indeed, this increase in 51 permeability was not likely due to disrupted endothelial cell-cell junctions since ZO-1 localization 52 revealed no visible changes in tight junction morphology, and treatment with the pro-inflammatory 53 factor TNF-α, known to disrupt both the EC GCX and EC junctions 33,34 , produced a much larger 6.9- 54 fold increase in permeability (not shown). Thus, it is likely that the increase in permeability observed 55 stemmed from increased diffusion of dextran across the degraded GCX layer between ECs through 56 depletion of its solid, charged fraction, thereby increasing the GCX inter-fiber spacing and mean free 57 path of the molecules 35,36 .…”
Section: Introductionmentioning
confidence: 95%
“…4a,b). An alternative 211 mechanism has been proposed in which CD44 on TCs binds to fibronectin deposited on ECs under 212 flow 54 . Yet, our data did not support this mechanism, whereby fibronectin was only localized on the 213 basal surface of the endothelium ( Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Many proteins are involved in CTC arrest at the surface of endothelial cells. In vivo experiments in zebrafish cancer models have shown that CTC arrest occurs in two steps: first by weak interactions via CD44 and the integrin αVβ3 and then by stronger attachment via the integrin α5β1 ( 74 ). Hydrodynamic forces also influence CTC arrest.…”
Section: Establishment Of the Tumor Microenvironment Arrest And Extmentioning
confidence: 99%